2019
DOI: 10.1093/ejo/cjz076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional orthodontic treatment on facial attractiveness of children with Class II division 1 malocclusion

Abstract: Summary Background/objectives Whether orthodontic treatment with functional appliances improves facial aesthetics is still under debate. This study aimed to determine whether functional orthodontic treatment improves the facial attractiveness of patients with Class II division 1 malocclusion. Materials/method Extraoral lateral photographs of 20 children with Class I (CLI, 11.7 ± 0.8 years), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 34 publications
4
31
0
2
Order By: Relevance
“…The results are also in accordance with two studies [20,37] that investigated the perception of facial attractiveness assessed by orthodontists, general pratictioners and laypersons after Herbst appliance treatment. Another study [38] reported no significant improvement in perceived facial changes after Class II treatment with functional appliances and fixed therapy, but the patients were not treated with the Herbst appliance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results are also in accordance with two studies [20,37] that investigated the perception of facial attractiveness assessed by orthodontists, general pratictioners and laypersons after Herbst appliance treatment. Another study [38] reported no significant improvement in perceived facial changes after Class II treatment with functional appliances and fixed therapy, but the patients were not treated with the Herbst appliance.…”
Section: Discussionsupporting
confidence: 90%
“…Although aesthetic improvement is the patient's primary goal, few studies have investigated the perception of profile and soft tissue improvements resulting from functional therapy [19,20]. Only one retrospective study investigated the effects of the Herbst appliance on the soft tissue profile by comparing it with an activator [21].…”
Section: Introductionmentioning
confidence: 99%
“…Um dos objetivos do tratamento da má oclusão de Classe II é a diminuição da convexidade facial, para essa fi nalidade são usados aparelhos funcionais (removíveis ou fi xos) ou a cirurgia ortognática para dar ao paciente um perfi l facial mais retilíneo com o avanço mandibular (VON BREMEN et al, 2014). A análise de alguns fatores como a idade do paciente, o tamanho da discrepância e a percepção do perfi l facial pelo paciente e seus pares são fundamentais para se chegar a um correto plano de tratamento (PADUANO et al, 2020).…”
Section: Introductionunclassified
“…[3][4] La hipertonicidad del mentón sugiere una incompetencia labial, ya que repercute en la estética facial, tomando en cuenta que actualmente ha aumentado su demanda en el número de pacientes, siendo este un factor re-levante para completar un tratamiento ortognático y de ortodoncia. [5][6] Hay más de veinte músculos en el rostro humano. Particularmente en el área de los labios y las mejillas; muchos músculos convergen o se entremezclan.…”
Section: Introductionunclassified
“…[3][4] Chin hypertonicity suggests a labial incompetence, since it affects facial aesthetics, taking into account that currently it has increased its demand in the number of patients, this being a re-lifting factor to complete an orthognathic and orthodontic treatment. [5][6] There are more than twenty muscles in the human face. Particularly in the area of the lips and cheeks; Many muscles converge or intermingle.…”
Section: Introductionmentioning
confidence: 99%